2022
DOI: 10.1038/s41467-022-35333-y
|View full text |Cite
|
Sign up to set email alerts
|

Focus image scanning microscopy for sharp and gentle super-resolved microscopy

Abstract: To date, the feasibility of super-resolution microscopy for imaging live and thick samples is still limited. Stimulated emission depletion (STED) microscopy requires high-intensity illumination to achieve sub-diffraction resolution, potentially introducing photodamage to live specimens. Moreover, the out-of-focus background may degrade the signal stemming from the focal plane. Here, we propose a new method to mitigate these limitations without drawbacks. First, we enhance a STED microscope with a detector arra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…It was found that (i) three processes, including nucleation, germination growth, and saturation stages, were found in the growth of CD-MOF⊃FL and the growth kinetics followed Avrami’s model, (ii) the dissolution rate at the face of a single CD-MOF⊃FL crystal was slower than that of its arris and the dissolution rate of the CD-MOF⊃FL crystal was increased with the increase of the water amount in methanol solution, and (iii) the dissolution process of the CD-MOF⊃FL crystal is a competitive process of erosion and diffusion in different methanol aqueous solutions and the dissolution kinetics followed the Korsmeyer–Peppas model. In this work, the spatial resolution of CLSM is limited at the micrometer scale, which can be improved by the employment of super-resolution reconstruction technology at the nanometer scale . These results offer new insights into the nature of dissolution kinetics of CD-MOF and provide new venues for the quantitative analysis of solid dissolution and growth at the single-particle level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that (i) three processes, including nucleation, germination growth, and saturation stages, were found in the growth of CD-MOF⊃FL and the growth kinetics followed Avrami’s model, (ii) the dissolution rate at the face of a single CD-MOF⊃FL crystal was slower than that of its arris and the dissolution rate of the CD-MOF⊃FL crystal was increased with the increase of the water amount in methanol solution, and (iii) the dissolution process of the CD-MOF⊃FL crystal is a competitive process of erosion and diffusion in different methanol aqueous solutions and the dissolution kinetics followed the Korsmeyer–Peppas model. In this work, the spatial resolution of CLSM is limited at the micrometer scale, which can be improved by the employment of super-resolution reconstruction technology at the nanometer scale . These results offer new insights into the nature of dissolution kinetics of CD-MOF and provide new venues for the quantitative analysis of solid dissolution and growth at the single-particle level.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the spatial resolution of CLSM is limited at the micrometer scale, which can be improved by the employment of super-resolution reconstruction technology at the nanometer scale. 54 These results offer new insights into the nature of dissolution kinetics of CD-MOF and provide new venues for the quantitative analysis of solid dissolution and growth at the single-particle level.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…However, in general, the signal collection capabilities of both central and edge detectors tend to become more similar as the defocus increases. The f-STED-ISM method removes the background of the STED using a square array detector. It supplied an adaptive background suppression method based on the linear ratio relationship between in-focus and out-of-focus Gaussian standard deviations.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, these methods require optically complex and cumbersome imaging processes, making them unfriendly to users and samples. A method termed as focus-image-scanning STED (f-STED-ISM) utilizes a cellular array detector to record the defocus information and remove the background disturbances of the image. However, this method does not work well when removing the peripheral inadequate-depletion fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of tailored data acquisition (DAQ) systems with these SPAD array detectors enables photon-resolved measurement of the fluorescence emission: every photon can be tagged with (i) spatial signatures, namely, the emission and detection coordinates of the photon in the detector and sample plane, respectively, and (ii) temporal signatures, namely, the time delay of the photon with respect to specific reference events. A series of recent publications 5 10 have demonstrated the benefits of leveraging the unique information provided by the SPAD arrays. The photon-resolved spatial and temporal information improves the performance of most advanced LSM-based techniques and paves the way for new ones.…”
Section: Introductionmentioning
confidence: 99%